Exercise as a Useful Intervention to Reduce Alcohol Consumption and Improve Physical Fitness in Individuals With Alcohol Use Disorder: A Systematic Review and Meta-Analysis - Lardier, David T.; Coakley, Kathryn E.; Holladay, Kelley R.; Amorim, Fabiano T.; Zuhl, Micah N. (Frontiers in Psychology, 2021)
Objective: This meta-analysis and systematic review examined the effects of exercise interventions on alcohol consumption and binge drinking in individuals with alcohol use disorder (AUD), alcohol abuse, or alcohol dependence, or harmful drinking. Data sources: PubMed, Web of Science, Google Scholar, SPORTDiscus, and ERIC databases. Study Inclusion and Exclusion Criteria: Peer-reviewed randomized controlled trials published in English between 1970 and 2021. All studies compared exercise (Ex) and treatment as usual (TAU) to TAU in adults with an alcohol-related diagnosis. All forms of exercise interventions were included (e.g., aerobic exercise, yoga, resistance exercise, etc.). Data Extraction: Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols standard and the Meta-Analyses and Systematic Reviews of Observational Studies guidelines were followed. Risk of bias was assessed using the Cochrane risk-of-bias tool as described by the Cochrane Handbook for Systematic Reviews and Interventions. Results: The literature searches retrieved a combined 2527 studies, with 1034 studies screened after removal of duplicates and 973 (94%) rejected after reviewing titles and abstracts. Full-text review was performed on 61 studies, with seven studies meeting inclusion criteria for qualitative and meta-analysis. Across seven studies (n= 492 participants), a significant effect (Z-value = -3.37; g= -0.30; 95% CI [-0.50 - -0.09]; p = 0.001) was found for Ex+TAU on drinking volume. There was no effect of Ex+TAU on binge drinking. The effect of Ex+TAU on physical fitness (VO2max, ml•kg-1•min-1) was significant (Z-score = 3.70; g = 0.64; 95% CI [0.19 – 1.08]; p<.001). Conclusions: Exercise interventions may decrease alcohol consumption and improve fitness and can be an effective adjunctive treatment for individuals with alcohol-related diagnoses including AUD and alcohol dependence.